EVALUATION AND CHARACTERIZATION OF SLEEPINESS IN MEDICAL RESIDENTS - Souto, Lucas Camargo; Siqueira, Bruna Machado; Botellho, Gabriel de Paula Barros; Lima, Luiz Felipe Torminn Rocha; Santos, Pedro Henrique dos; Silva, Wesley Gomes da (CIPEEX, 2025)
The purpose of the present study is to evaluate and characterize sleepiness in medical residents and its relationship with sleep deprivation and clinical decision-making, in addition to comparing the prevalence and effect of sleepiness among residents of different specialties. Three validated instruments were used: the Epworth Sleepiness Scale (ESS) to assess daytime sleepiness, the Pittsburgh Sleep Quality Index (PSQI) to measure sleep quality, and the Melbourne Decision-Making Questionnaire (MDMQ) to identify decision-making profiles. The questionnaires were applied before and after hospital shifts, allowing the analysis of variation in sleepiness throughout the day. The results showed a high prevalence of excessive sleepiness among residents, especially in specialties with night shifts. Sleep deprivation was associated with poorer sleep quality and reduced decision-making capacity. Despite sleepiness, residents maintained a vigilant decision-making pattern, possibly as a compensatory mechanism. It is concluded that excessive sleepiness negatively affects residents, especially those with more night shifts, and may compromise clinical decision-making. This suggests the need for measures to monitor and reduce risk factors, improve mental health and quality of life of professionals, and reassess workload.